THE MILLSTONES OF PETROTA THRACE COUNTY, GREECE - Κοσιάρης, Γ.; Μιχαήλ, Κ. (Bulletin of the Geological Society of Greece, 2004)
The surrounding area of Petrota village - Rhodopi County, West Thrace - consists , mainly, of volcanic rocks (rhyolites, rhyodacites, tuffs, volcanic breccias and lahars). In the pyroclastic formations a quarry for millstones has been developed. Engraved or halfcarved handmills, larger millstones, tubs and cisterns can be seen and they are witnesses of the art and skill of the stone cutters. Larger millstones which needed animal or water power to be rotate were also carved. Some of them are abandoned on the floor of the quarry or lay lower near the river bank. On the quarry walls can be seen all the stages of carving and cuttering the millstones : a drawing circle - the first stage, close to it the beginning of the carving and nearby the fully carved but still uncuttered millstones. Amazing is also the underground quarrying and carving the millostones. Having in mind the size of the walls, the underground excavation and the bulk of dums we can roughly estimate the number of carved millstones which probably reaches several thousands of millstones of different sizes. The beginning of quarrying and carving of millstones of Petrota is not known but surely it could be traced back to the depth of the ages, not excluding the prehistoric period. The activity of the quarry ended a little before the II World War. A similar quarry in almost the same rock is located near the Petrota village of Evros County.